Characterization And Alkaline Fusion Recovery Process Of Rare Earths And Thorium From Malaysian Monazite - Udayakumar, Sanjith (2019)
The use of edges to determine an optimal region of interest (ROI) location is increasingly becoming popular for image deblurring. Recent studies have shown that regions with strong edges tend to produce better deblurring results. In this study, a direct method for ROI localization based on edge refinement filter and entropy-based measurement is proposed. Using this method, the randomness of grey level distribution is quantitatively measured, from which the ROI is determined. This method has low computation cost since it contains no matrix operations. The proposed method has been tested using three sets of test images - Dataset I, II and III. Empirical results suggest that the improved edge refinement filter is competitive when compared to the established edge detection schemes and achieves better performance in the Pratt's figure-of-merit (PFoM) and the twofold consensus ground truth (TCGT); averaging at 15.7 % and 28.7 %, respectively. The novelty of the proposed approach lies in the use of this improved filtering strategy for accurate estimation of point spread function (PSF), and hence, a more precise image restoration. As a result, the proposed solutions compare favourably against existing techniques with the peak signal-to-noise ratio (PSNR), kernel similarity (KS) index, and error ratio (ER) averaging at 24.8 dB, 0.6 and 1.4, respectively. Additional experiments involving real blurred images demonstrated the competitiveness of the proposed approach in performing restoration in the absent of PSF.